Isolation and Purification of Antiplasmins from Human Granulocytes - Wołosowicz, N; Prokopowicz, J (Thrombosis and Haemostasis, 1970)
Two antiplasmins were found in human granulocytes. Chromatography on Sephadex G-200 showed 3 peaks with antiplasmin activity. One immediately acting antiplasmin and 2 progressively acting antiplasmin (I and II) have been identified. The immediate antiplasmin was purified 92-fold, the progressive antiplasmin 1129-fold and progressive antiplasmin II 185-fold. Disc electrophoresis showed homogeneity of the fractions. They were found to migrate with the alpha-2 globulin fraction. The physiological function of the antiplasmins is briefly discussed.